Errata - Editorial Office (Ukrainian Antarctic Journal, 2009)
Correction to the article by V.I. Bogillo and M.S. Bazylevska "The interaction of chlororganic pollutants with snow cover in Antarctica", published in the Ukrainian Antarctic Journal № 6-7 (pp. 119-134).